Now a university! SKSU print materials a print production research - Narcilla, Princess Melody L.
Sultan Kudarat State University (SKSU), the institution of higher learning in Region 12 especially in Sultan Kudarat Province aims to perpetually offer relevant and quality education for the development of a rigorous and productive human resource. It was formerly Sultan Kudarat Polytechnic State College (SKPSC); and last 2010, Republic Act 9966 converted SKPSC into a state university. Because of the large transition faced by the institution, there is a need for it to introduce and establish itself from being a state college to a university to the public. The institution needs to device larger public relations and advertisement strategies that would not only help in disseminating the information about the transition, but more importantly in persuading the target audience to enroll and study at SKSU. This study is a print production thesis that would create print materials for SKSU in the form of brochures. The purpose of this study is to establish the transition of SKSU from a state college to a university along with the improvements in the institution?s programs, teaching methods, and facilities. Furthermore, the print materials aim to establish the identity of each of the ten SKSU campuses based on their respective fields of specialization, and at the same time, uniting all the campuses under one umbrella of SKSU. All these lead to the goal of convincing the target audience who are the third year and fourth year high school students in Sultan Kudarat Province to enroll in SKSU rather than going to faraway places to study
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts